Comprehensive measurement of purines in biological samples - Fu, Rong; Sutcliffe, Diane J.; Dinasarapu, Ashok R.; Hess, Ellen J.; Jinnah, H. A. (Frontiers in Analytical Science, 2025)
Defects in numerous aspects of purine metabolism are well-recognized causes for human diseases. The applicability of ultra performance liquid chromatography (UPLC) with photodiode array (PDA) detection for analysis of the most abundant biological relevant purines metabolites is described. This method was optimized to resolve and quantify 15 purine metabolites including ATP, ADP, AMP, adenosine, adenine, GTP, GDP, GMP, IMP, ZMP, guanosine, hypoxanthine, inosine, xanthine and uric acid in 33 min with a 5 μL injection volume. With purified standards, the detection was linear in a range from 0.1 to 100 μM. The within-run and between-run variances were <2% overall, indicating excellent reproducibility and reliability. Samples from cultured human cells were prepared to assess the applicability of the method in biological samples. When compared to normal cell lines, mutant cell lines in which purine salvage was absent showed small or no changes for most intracellular purines. Conditioned medium contained no detectable purines, except for hypoxanthine, which was elevated in the mutant lines as expected. Compared to previous methods, this new UPLC-PDA method provides better resolution of key purine metabolites, higher sensitivity with a smaller sample size and half the run time. Similar to prior methods, the new method appears well suited to the simultaneous analysis of the most abundant biologically relevant purines in biological samples.